Teacher Perceptions on the Use of 5E Learning Cycle Model in Social Studies Courses - Sagdic, Mustafa; Koçoğlu, Erol (Journal of History Culture and Art Research, 2020)
Several methods are used to improve meaningful learning levels of students in learning environment during the social studies course learning-instruction process. The 5E instruction method is among these models. One of the constructivist instructional approaches, the 5E method is an ancillary and regulatory model for teachers who are the leaders in the learning-instruction process. This model, which is significant for teachers, includes a number of stages. Conducting active and effective activities during these stages depends on the organization and transfer of the course activities to the stages of this learning cycle. The aim of the present study was to determine the perceptions of social studies teachers on the use of the 5E learning cycle method in social studies courses. In the present study that aimed to tackle perceptual analysis with a qualitative approach, the phenomenology design that was deemed adequate for the nature of the study topic was utilized. A semi-structured interview form developed by the authors was used to collect the study data. The study group members, whose perceptions on the research topic were obtained with the semi-structured interview form, included social studies teachers employed in various public middle schools in Malatya province, Turkey. NVivo 11 analysis software was used to assess and analyze the study data based on the sub-themes. The study findings demonstrated that social studies teachers had interesting perceptions on the study topic.